Three pediatric patients with primary hyperparathyroidism caused by parathyroid adenoma - Arum Oh; Yena Lee; Han-Wook Yoo; Jin-Ho Choi (Korean Society of Pediatric Endocrinology, 2021)
Primary hyperparathyroidism (PHPT) is a hypercalcemia disorder with inappropriately normal or increased serum parathyroid hormone (PTH) levels resulting from excessive secretion of PTH from one or more of the parathyroid glands. PHPT is uncommon in infants and children, with an estimated incidence of 2-5 cases per 100,000 persons. Patients with PHPT usually present with bone pain, urolithiasis, or nephrolithiasis, as well as nonspecific symptoms such as fatigue and weakness. Asymptomatic hypercalcemia may also be detected incidentally. Only a few cases of pediatric PHPT have been reported in Korea. We present three patients (a 9-year-old girl, a 14-year-old boy, and a 14-year-old girl) with PHPT who manifested variable clinical features of hypercalcemia. The first and second patients each had a parathyroid adenoma and presented with abdominal pain caused by pancreatitis and a ureter stone, respectively. The third patient had an ectopic mediastinal parathyroid adenoma and presented with gait disturbance and weakness of the lower extremities. All of the patients underwent surgical resection of parathyroid adenoma, and their serum calcium levels subsequently normalized without medication.